2018
DOI: 10.31665/jfb.2018.2145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of food-derived peptides in human blood after ingestion of corn and wheat gluten hydrolysates

Abstract: Bioactive peptides in the body after ingestion of plant protein hydrolysates have been speculated but not identified. We aimed to establish an approach to identify small amounts of food-derived peptides in humans after ingestion of non-extracellular matrix protein hydrolysates. Corn and wheat gluten hydrolysates were digested using pancreatin and leucine aminopeptidase; the resultant peptides were identified via size-exclusion chromatography and reverse-phase HPLC-tandem mass spectrometry (MS/MS). Structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…In addition, various peptides can be transported across the intestinal epithelial membrane. This is the case was derived-milk peptides or corn and wheat gluten hydrolysates, which have been identified in the human bloodstain after ingestion [57,58]. Common peptide transport routes are at circulating bloodstain carrier-mediated permeation, transcytosis, paracellular transport or passive diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, various peptides can be transported across the intestinal epithelial membrane. This is the case was derived-milk peptides or corn and wheat gluten hydrolysates, which have been identified in the human bloodstain after ingestion [57,58]. Common peptide transport routes are at circulating bloodstain carrier-mediated permeation, transcytosis, paracellular transport or passive diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there is no study demonstrating the enhancement of the production of host antimicrobial peptides by the oral administration of a single food component. It has been shown that pyroGlu-Leu is widely distributed in food protein hydrolysates, such as wheat gluten and corn gluten hydrolysates, 7 as well as in Japanese fermented foods produced by Asperigillus oryzae , such as the Japanese rice wine known as sake, the salted fermented soy paste known as miso, and a type of soy sauce, shoyu. 15 Fermented foods are consumed in the diet, while protein hydrolysates are generally consumed as supplement.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Food protein hydrolysates and fermented foods contain pyroglutamyl peptides, which are spontaneously generated from peptides with a glutaminyl residue at the amino terminal during storage and processing. 57 Short chain pyroglutamyl peptides are resistant to digestion by endoproteinases and exopeptidases. Some of the short chain pyroglutamyl peptides have been demonstrated to have in vivo 811 and in vitro 12,13 activities.…”
Section: Introductionmentioning
confidence: 99%
“…To improve resolution and detection of compounds with primary and secondary amines, derivatization with AccQ, followed by LC-MS/MS, was performed (Ejima et al, 2018). Aliquots (200 μL) of SEC fractions were dried under vacuum.…”
Section: Liquid Chromatography-tandem Mass Spectrometry (Lc-ms/ms) Anmentioning
confidence: 99%